2022
DOI: 10.3389/fmicb.2022.991818
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional alterations of intestinal flora in mice induced by halonitromethanes exposure

Abstract: Halonitromethanes (HNMs) as one typical class of nitrogenous disinfection byproducts (DBPs) have been widely found in drinking water and are receiving more and more attentions because of their high cytotoxicity, genotoxicity, and developmental toxicity. However, the effects of HNMs exposure on the intestinal tract and intestinal flora remain unknown. This study comprehensively determined the effects of trichloronitromethane, bromonitromethane, and bromochloronitromethane exposure on the intestinal tract and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Some studies have shown that DBPs could disrupt the balance of the microbial community and lead to dysbiosis. , However, it is unclear whether the lasting effects of DBPs on the gastrointestinal tract are related to DBP-induced dysbiosis. In this study, SHIME colonizing the gut microbiota made it possible to study the relationship among DBPs, the gut microbiota, and the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that DBPs could disrupt the balance of the microbial community and lead to dysbiosis. , However, it is unclear whether the lasting effects of DBPs on the gastrointestinal tract are related to DBP-induced dysbiosis. In this study, SHIME colonizing the gut microbiota made it possible to study the relationship among DBPs, the gut microbiota, and the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…13 Several studies have shown that DBP exposure could affect the structure and function of the gut microbiota. 14,15 However, there are few reports on how exposure to DBPs affects the gut microbiota and thus indirectly produces enterotoxic effects. Due to the infeasibility of human exposure tests and ethical issues, the in vitro gastrointestinal simulation test method provides an opportunity to study the degradation of environmental contaminants in the gastrointestinal tract.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation